Ultrastructural analysis of explanted CyPass microstents and correlation with clinical findings - Hübner, Lisa; Schlötzer-Schrehardt, Ursula; Weller, Julia; Hohberger, Bettina; Mardin, Christian; Lämmer, Robert (Graefes Archive For Clinical and Experimental Ophthalmology, 2022)
Purpose: The purpose of this study was to obtain insight into cellular processes after CyPass microstent implantation into the supraciliary space. With this knowledge, we expected to find some reason for surgical failure. Methods: Nine CyPass microstents of 8 patients with primary open-angle glaucoma (n = 1), pseudoexfoliation glaucoma (n = 5), uveitic glaucoma (n = 1), and posttraumatic open-angle glaucoma (n = 1) were explanted due to recurrence of IOP elevation, corneal decompensation, or persistent hypotony. The explants were processed for light and transmission electron microscopy. Results: Fibrotic material, consisting of collagen fibrils, microfibrils, pseudoexfoliation fibrils produced by activated fibroblasts, was detected in the stent lumen of 4/5 pseudoexfoliation glaucoma patients and also in posttraumatic open-angle glaucoma. Fibrotic material was also present on the outer surface and within fenestrations of the majority of stents. Complete absence of fibrotic reaction was noticed in 3 of 9 microstents. Conclusion: Although MIGS is known to be less invasive than conventional surgery, implants placed in the suprachoroidal space may be adversely affected by a fibrotic tissue reaction resulting in implant failure. Understanding mechanisms and risk factors leading to fibrotic scarring following antiglaucomatous surgery may help to develop novel strategies that improve surgical outcome.
CRIS-Team Scopus Importer:2022-03-18
Keywords: CyPass microstent; Fibrosis; Glaucoma; MIGS; Surgery failure